2010
DOI: 10.2478/s11535-010-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

L-rhamnose and L-fucose suppress cancer growth in mice

Abstract: It is documented that deficient fucosylation may play an important role in the pathogenesis of cancer. Since the supplementation ofL-fucosecouldrestorefucosylationinbothin vitro and in vivoconditions,ourintentwastoexaminetheeffectofintraperitoneal administration of L-fucose and L-rhamnose (a similar deoxysaccharide) on tumour growth, mitotic activity and metastatic setting ofasolidformofEhrlichcarcinomaaswellasonthesurvivalrateoftumourbearingmice.BothL-fucoseandL-rhamnoseexerted a significant suppressive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
(41 reference statements)
2
26
0
1
Order By: Relevance
“…The differences in glucuronic acid quantities between the cultures were consistent with the decrease in zeta potential values. Interestingly, a significant increase in glucose and galactose residues (5-and 2-fold increases, respectively) and the presence of rhamnose (1.5 mol%), a neutral sugar with immunosuppressor activity (45), were detected in capsular PS isolated from the chronologically old culture.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in glucuronic acid quantities between the cultures were consistent with the decrease in zeta potential values. Interestingly, a significant increase in glucose and galactose residues (5-and 2-fold increases, respectively) and the presence of rhamnose (1.5 mol%), a neutral sugar with immunosuppressor activity (45), were detected in capsular PS isolated from the chronologically old culture.…”
Section: Resultsmentioning
confidence: 99%
“…35 The potential value for therapy is enhanced by lack of toxicity observed in our mice and in previously reported animal and human studies. 36 Additionally, low-molecular-weight fucoidan (LMWF), a group of fucose-enriched sulphated polysaccharides extracted from seaweed, was shown to have a protective effect on I/R injury in mice, 37 though the mechanism was not fully explained. 25 Previous cancer studies have shown that IP injections of l-fucose are not detrimental in mice up to a level of 5 g/kg (approximately 160 mg).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, oral administration of L-fucose was found to successfully increase fucosylation in the patient with leukocyte adhesion deficiency type II (LAD II), a rare inherited disorder of fucose metabolism [51][52][53]. Moreover, tumour growth, mitotic activity and metastatic setting were greatly suppressed by daily intraperitoneal injection of L-fucose in the Ehrlich carcinoma mice [53]. Our results further suggest that the sensitivity to TRAIL can be simulated after elevated expression of FUT3 or FUT6 in tumour cells, which is mainly mediated via DR5 as evidenced by the enhanced sensitivity to DHER of these cells.…”
Section: Discussionmentioning
confidence: 99%